Impact of Indigenous Practices in School Leadership: A Phenomenological Study of Community Schools - Sherpa, Dawa; Baraily, Khagendra; Rai, Bharat (NCC Journal, 2024)
This paper aims to explore the influences of indigenous practices of the Sherpa community in school leadership. Purposely four Sherpa head teachers with more than five years of experience were selected from the Dolakha district. In-depth interviews were conducted for the information collection and head teachers day to day activities and their decision-making and administrative practices were observed and maintained diary. The interview records and diary notes were transcribed and developed code. Themes were developed using a similar code and analyzed thematically. The study found that Indigenous school leadership enhanced their indigenous knowledge, values, and culture in school. It promotes inclusiveness and equity in the school. The Sherpa community has a strong belief system of rebirth. Taking something from others is a sin, and enjoy donating poor and backwards. Indigenous leaders are found more accountable and transparent in the school administrative process.